A Construção da Identidade das Meninas Negras na Escola: Mídias e Representatividade - Medeiros, Jeane Cristina (2021)
This paper aims to analyze how school and the media can contribute to the construction and strengthening of the identity of black girls in Brazil. Empirical research, as well as action research and observation techniques, was used as a methodological support. The theoretical categories of this ethnic-racial study dialogued with intellectuals who will be highlighted here. Alves (2000, 2003) and DURAN (2007) were used in the treatment of school routine, while barbosa's contributions (2016) made it possible to uncover racial theories and colonialism. Alluded to the tripod identity, culture and aesthetics, gonzalez (1984, 1988), CARNEIRO (2003) and GOMES (2008, 2010) references were used as references. And in the treatment of the place of speech in the school context, it was corroborated by ribeiro's perspectives (2017). We highlight in due course the research carried out in important documents for this context, including the National Plan for the Implementation of the National Curriculum Guidelines for the Education of Ethnicorracial Relations and for the Teaching of Afro-Brazilian and African History, as well as the normative collection available in laws 9.394/96 (LDBE) and law 10.639/03. Regarding action research, the empirical field was the Municipal School Professor Mateus Viana, located in the city of Caicó/RN, where it was possible to observe a scenario of 15 students and students of the 5th year, in which 73% presented black phenotypic traits. For the purposes of the research, we analyzed the black girls who made up this classroom, and identified themselves through the performance of pedagogical activities, that they were ugly when they saw their image reflected in the mirror. Finally, it is considered that it is possible to infer that schools and the media still as invizibilizers of black girls, not recognizing them as protagonists in these spaces.